2013
DOI: 10.1007/s11745-013-3809-z
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro TNF‐α‐ and Noradrenaline‐Stimulated Lipolysis is Impaired in Adipocytes from Growing Rats Fed a Low‐Protein, High‐Carbohydrate Diet

Abstract: The aim of this study was to investigate tumor necrosis factor alpha (TNF-α)- and noradrenaline (NE)-stimulated lipolysis in retroperitoneal (RWAT) and epididymal (EAT) white adipose tissue as a means of understanding how low-protein, high-carbohydrate (LPHC) diet-fed rats maintain their lipid storage in a catabolic environment (marked by increases in serum TNF-α and corticosterone and sympathetic flux to RWAT and EAT), as previously observed. Adipocytes or tissues from the RWAT and EAT of rats fed an LPHC die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The increase in ATGL and the phospho-AMPK/AMPK ratio in the ingWAT of LPHC diet-fed rats suggested increased lipolysis in the tissue, although no changes were observed in HSL level. These enzymes act sequentially; although ATGL has a high affinity for TG, HSL has a high affinity for diacylglycerol (DAG) [16]. Studies have shown that the activity of ATGL is increased following phosphorylation at Ser406 by AMPK [45] and that depletion of AMPK promotes a reduction in the phosphorylation and activity of ATGL [46].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The increase in ATGL and the phospho-AMPK/AMPK ratio in the ingWAT of LPHC diet-fed rats suggested increased lipolysis in the tissue, although no changes were observed in HSL level. These enzymes act sequentially; although ATGL has a high affinity for TG, HSL has a high affinity for diacylglycerol (DAG) [16]. Studies have shown that the activity of ATGL is increased following phosphorylation at Ser406 by AMPK [45] and that depletion of AMPK promotes a reduction in the phosphorylation and activity of ATGL [46].…”
Section: Discussionmentioning
confidence: 99%
“…Male Wistar rats weighing approximately 100 g (30 to 32 d old) were randomized into either the C group or the LPHC group. Rats in the C group were fed a diet containing 17% protein, 63% carbohydrates, and 7% lipids [25], and those in the LPHC group were fed a diet containing 6% protein, 74% carbohydrates, and 7% lipids for 15 d. The diets were isocaloric (16.3 kJ$g -1 ), with the energy difference from the reduction in dietary protein compensated for by increasing the carbohydrate content [13][14][15][16][17][18][19][20][21][22][23]25] (Table 1). The rats were individually housed in metabolic cages in an environmentally controlled room (lights on from 0600 to 1800; temperature 22 AE 1 C).…”
Section: Animals and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Our laboratory has investigated the effects of a low protein, high-carbohydrate (LPHC) diet in rats [22][23][24][25][26][27][28][29] because the nutrition of children, after weaning, across the Western world is rich in carbohydrates and poor in protein content [30,31]. The administration of this diet to young rats (soon after weaning) promotes an increase in their food and calorie intake.…”
Section: Introductionmentioning
confidence: 99%